Marxismo, ideología y experiencia en el debate entre las FAR y el PRT-ERP - Esteban Campos (Nuevo mundo - Mundos Nuevos, 2013)
The purpose of this paper is to explore the main argumentative cores of the debate between the Fuerzas Armadas Revolucionarias (FAR) and the Partido Revolucionario de los Trabajadores-Ejército Revolucionario del Pueblo (PRT-ERP), two armed groups that operated in Argentina in the 1970s. The discussion took place between April and November 1971, and its trigger was the publication of an extensive interview to the FAR in the review Cristianismo y Revolución. This interview was answered by a document issued by a group of prisoners held in ERP Jail Accused of Cordoba, which had in turn in reply a letter from the leader of the FAR Carlos Olmedo, the "Contributions to the process of confrontation positions and public controversy boarded with ERP ". While we consider this duel discourse as one of the highest points of political exchange, ideological and cultural guerrillas into Argentina, we want to avoid the cliches of the debate between left and Peronism. We prefer instead to analyze the internal logic of each argument from a critical perspective, without falling into the apology or censorship of political-military organizations. In this article we will promptly investigate the role attributed to the three discussion documents Marxism, ideology and experience. We want to study the meaning of these categories from the point of view of historical actors, as well as track where ideological and discursive constellation are located, to practice and readings are sent.